Characteristics of adipocytokine expression by local fat depots of the heart: Relationship with the main risk factors for cardio-vascular diseases - Gruzdeva, Olga V.; Dyleva, Yulia A.; Belik, Ekaterina V.; Sinitsky, Maxim Yu.; Kozyrin, Kiril A.; Barbarash, Olga L. (Frontiers in Endocrinology, 2022)
Purpose: to evaluate the gene expression of adiponectin, leptin, its soluble receptor and interleukin 6 (IL-6) in epicardial (EAT), perivascular AT (PVAT), subcutaneous adipose tissue (SAT) and their relationship with the main cardiovascular diseases (CVD) risk factors in patients with coronary artery disease (CAD). Methods: fat tissue biopsies were obtained from 134 patients with stable CAD undergoing coronary artery bypass grafting and 120 patients undergoing aortic or mitral valve replacement. Adipocytes were isolated from SAT, EAT, and AT (PVAT) samples, and cultured for 24 h, after which gene expression of adipocytokines in the culture medium was determined. Results: men showed reduced ADIPOQ expression in EAT and PVAT, LEP expression in PVAT, and LEPR expression in SAT and PVAT compared to women. Men also exhibited higher SAT and lower PVAT IL6 than women. Meanwhile, dyslipidemia associated with decreased ADIPOQ expression in EAT and PVAT, LEPR in EAT, and IL6 in PVAT. Arterial hypertension (AH) associated with low EAT and PVAT ADIPOQ, and high EAT LEP, SAT, as well as PVAT LEPR, and IL6 in SAT and EAT. ADIPOQ expression decreased with increased AH duration over 20 years against an increased LEP background in ATs. Smoking increased ADIPOQ expression in all ATs and increased LEP in SAT and EAT, however, decreased LEPR in PVAT. Patients 51–59 years old exhibited the highest EAT and PVAT LEP, IL-6, and LEPR expression compared to other age groups. Conclusions: decreased EAT ADIPOQ expression against an increased pro-inflammatory IL6 background may increase atherogenesis and contribute to CAD progression in combination with risk factors including male sex, dyslipidemia, and AH.